INOVASI PELAPORAN KEUANGAN BERBASIS KEBERLANJUTAN SEBAGAI STRATEGI NILAI JANGKA PANJANG - Paryati, Retno; Syafwan, Elvathna; Rostiawati, Iis (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
This study is driven by the growing demand for corporate transparency and accountability, which no longer focuses solely on financial performance but also encompasses environmental, social, and governance (ESG) dimensions as an integral part of sustainability principles. Within this framework, sustainability-based financial reporting has emerged as a strategic innovation with the potential to generate long-term value for all stakeholders. This study aims to examine the role and effectiveness of sustainability-based financial reporting in enhancing corporate value in a sustainable manner. The method employed is a qualitative approach with a descriptive-analytical design, utilizing literature reviews, document analysis, and an examination of sustainability reporting practices across various organizations. The findings indicate that the application of sustainability principles in financial reporting enhances investor confidence, strengthens corporate reputation, and supports more comprehensive decision-making processes. In addition, innovations in this reporting system encourage companies to be more adaptive to various long-term risks, including climate change and social developments. The discussion underscores that sustainability-based reporting serves not only as a medium for conveying information but also as a strategic tool for building competitive advantage. Thus, it can be concluded that the implementation of sustainability-based financial reporting is an appropriate and effective strategy for creating long-term corporate value, making it worthy of broader adoption by organizations across various sectors.